Faktor Yang Mempengaruhi Repurchase Intention Pada Coffeshop Di Kota Batam Dengan Customer Satisfaction Sebagai Mediasi - Seren, Seren; Christiarini, Renny (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
Coffee is an agricultural product highly favored by many people and has a vast market potential. The population in Indonesia, especially in Batam City, supports the high consumption of coffee. Due to the increasing interest in coffee and the high coffee consumption in Indonesia, numerous coffee shops, both national and international, have started opening outlets in Indonesia, especially in Batam City. The purpose of this research is to analyze the factors that can influence Repurchase Intention in coffee shops in Batam City. Data were collected from 102 residents of Batam City aged 17-30 years who frequently visit and purchase products from coffee shops in Batam City using judgmental sampling through a Google Form survey. Data analysis was conducted using partial least squares - structural equation modeling (PLS-SEM). The results of the research indicate that product quality, service quality, brand image, e-wom (electronic word-of-mouth), and Atmosphere have a significant positive influence on customer satisfaction. Customer satisfaction also mediates the relationship between product quality, service quality, brand image, e-wom, Atmosphere, and Repurchase Intention. The findings of this study can serve as a reference for coffee shop owners in enhancing customers' intention to repurchase their products and overall customer satisfaction.